Pengaruh Sistem Penilaian Kinerja Terhadap Perilaku Manajer Tingkat Menengah Pada PT. Bank "X" - Abukosim Abukosim (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2009)
Designing the system of management performance evaluation is critical for organizations or enterprises to maximize organizational outcomes, and it can cause behavioral impact to the managers who are being evaluated. The conviction rate to the accounting information as performance evaluation criteria is called RAPM rate (reliance on accounting performance measure). On the certain conditions, using accounting information as performance evaluation criteria (high RAPM rate) could cause the rise of dysfunctional behavior on the managers who are being evaluated. The research aimed to know RAPM rate on the performance evaluation of the middle managers in PT. Bank “X”, and to know effect RAPM rate to behavior of middle managers evaluated. This research used survey method. Population being researched is middle managers in PT. Bank “X”. Data found by giving questionnaire to the respondent, interview, and some secondary data. The research result shows that; the system of management performance evaluation which is applied to evaluate the achievement of middle managers in PT. Bank “X” exploit accounting and non-accounting information as performance evaluation criteria.Key Words: Performance evaluation criteria, Dysfunctional behavior